Precarious Oceans and Vulnerability: Micropolitics of Care in Romesh Gunesekera’s Reef - Ghosal, Abhisek (SARE: Southeast Asian Review of English, 2024)
Inoperative grammatology of post(g)locality followed by the incremental desires of neoliberal elites to marketize abundant oceanic resources scattered across the world renders the oceans extremely vulnerable—an appalling phenomenon which at once lays bare the vulnerability of the oceans conditioned by the strands of ‘precariousness’ and at times calls for the actualization of ‘micropolitics of care’—an ethically sound exercise which seems to be able to hold the oceans back from being economically subjected to the predatory ‘faces’ of contemporary neoliberal precarity. In this context, Romesh Gunesekera’s Reef is critically taken up to examine the rapid disappearance of coral reefs along with the illegal marketing of endangered marine species like dolphin so as to make readers aware of how the ocean stands at risk and moreover to put literary emphasis on the enactment of ‘micropolitics of care’ which seems to be able to effectively take on the wicked designs of contemporary neoliberal precarity for the greater sake of planetary consciousness.